Methylation in the p53 promoter in epithelial ovarian cancer - Chmelarova, Marcela; Krepinska, E; Spacek, J; Laco, J; Beranek, M; Palicka, V (Clinical & translational oncology., 2013)
OBJECTIVE: Ovarian cancer is a leading cause of death from gynecologic tumors, however, the molecular and especially epigenetic events underlying this transformation are poorly understood. Promoter methylation status of tumor suppressor genes may be associated with transcriptional silencing and tumor progression. It has been shown that methylation of CpG dinucleotides located in the promoter region of p53 is associated with low expression levels of this gene. The aim of this study was to investigate promoter methylation of p53 gene in ovarian cancer by comparison with normal ovarian tissue. METHODS: To search for promoter methylation of p53 gene we used methylation-specific PCR (MSP) to compare the methylation status of 66 tissue samples of ovarian cancer with 37 control samples. RESULTS: In our study methylation specific PCR revealed p53 promoter methylation in 34 of 66 (51.5 %) of specimens with ovarian cancer. CONCLUSION: These results indicate that methylation in p53 promoter region may play an important role in carcinogenesis of ovarian cancer and could potentially be used in screening of ovarian cancer, and may have implications for future chemotherapy based on epigenetic changes.
Keywords: Humans; Neoplasms, Glandular and Epithelial; polymerázová řetězová reakce; Polymerase Chain Reaction; lidé; promotorové oblasti (genetika); ženské pohlaví; Promoter Regions, Genetic; nádorový supresorový protein p53; Tumor Suppressor Protein p53; metylace DNA; nádory glandulární a epitelové; Ovarian Neoplasms; nádory vaječníků; Female; DNA Methylation